ASSOCIATION BETWEEN THE WEIGHT LOSS AND ANXIETY, DEPRESSION AFTER PERCUTANEOUS TRANSLUMINAL CORONARY ANGIOPLASTY: A NEED FOR PRE-DISCHARGED COUNSELING - Shetty, Prasad N; Tom, Devasia; Rao K, Yeshwanth; Singh, Ajit; Karim, Hasheer (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To see the association between weight loss and anxiety, depression after percutaneous transluminal coronary angioplasty (PTCA) for coronary artery disease patients. (1) To see the severity of anxiety and depression 1 month after PTCA, (2) to evaluate the relationship between the weight changes and major adverse cardiac events (MACE) in 1 month follow-up. Methods: A total 1001 patients who underwent PTCA for acute coronary syndrome and coronary heart disease were included. Data were collected at baseline and 1 month after PTCA. A validated Euro 5Q-5D-5L questionnaire was used to assess the level of anxiety and depression. Chi-square test was applied to find out the association between weight loss status and anxiety, depression. Results: There was a significant decrease in mean weight 1 month after coronary angioplasty (64.18Â±11.022 vs. 61.96Â±11.17, p<0.001). No association was observed between weight loss status and anxiety, depression in PTCA patients (p=0.5) and there is no significant association between weight changes and MACE 1 month after PTCA (p=0.92). Conclusion: Data show that anxiety and depression were observed in 64.9% of the study population after coronary angioplasty but anxiety and depression are not associated with weight loss after PTCA. Loss of weight may be due to the modified post angioplasty lifestyles such as adherent to Mediterranean diet, physical exercise, cessation of smoking, optimum control of blood pressure, blood sugar, and blood cholesterol along with prescribed medications. Anxiety and depression may turn into chronic stage if not treated wisely could lead to significant MACE. Proper pre-hospital discharge counseling is necessary for all post PTCA patients to sustain their quality of life.